Formability and Mechanical Properties of Polyvinyl Chloride (PVC) in the Thermoforming Process - Rahmadi Nurapela Nugraha; Arianto Leman Soemowidagdo; Prihatno Kusdiarto (Program Studi Sarjana Terapan Teknik Mesin, Fakultas Vokasi, Universitas Negeri Yogyakarta, 2025)
This study investigated the effects of polyvinyl chloride (PVC) sheet thickness and heating temperature on formability, tensile properties, and thickness shrinkage in the thermoforming process. PVC sheets with thicknesses of 0.15, 0.20, and 0.25 mm were processed at 140, 160, and 170 °C. The experiment consisted of nine treatment combinations, with three repetitions for each combination, giving a total of 27 specimens. Data were obtained by observing the formability of the thermoformed products, measuring tensile properties using a universal testing machine, and measuring thickness changes using a digital microscope and a thickness gauge. The results show that both thickness and temperature affect the thermoformability and mechanical performance of PVC sheets. The highest tensile strength after thermoforming was obtained at a thickness of 0.25 mm and a temperature of 140 °C, with a stress value of 42.7 MPa or a maximum load of 4.30 kgf. Increasing the forming temperature reduced tensile strength, particularly for thinner materials. The greatest shrinkage was 53.3%, observed at a thickness of 0.15 mm and a temperature of 170 °C. Overall, thinner PVC sheets formed more easily at higher temperatures, but they also experienced greater shrinkage and lower tensile strength